(untitled) (Eurasian Scientific Herald, 2023)
The article describes the features of the development of mental processes in primary school students and how they manifest themselves in the process of cognition and understanding of nature. He also details the strengthening and development of key characteristics of cognitive processes, such as cognition, attention, memory, imagination, thinking and speech, in the early school years.